Analisis Internet Speed Test dalam Performa Akses pada Fast.com - Julianto, Julianto (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Fast.com is a popular speed testing tool on the internet that allows users to measure download and upload speeds quickly and accurately. The research approach used in this research is a qualitative approach, while the methods used are literature studies and experiments. The research results show that fast.com is a site used to measure internet speed, especially download speed, where the features and services are easy to understand, without advertising and without complicated settings, so it is very easy to use and the measurement results can be used to evaluate the performance of service providers. internet (ISP) and determine whether the speed provided meets the user's needs.